Pengaruh pemberian prenatal yoga dengan tingkat cemas ibu hamil menghadapi persalinan - Rischa Laura Agus Miana; Nita Evrianasari; Anggraini Anggraini (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2022)
Effects of yoga relaxation on anxiety levels among pregnant women on the preparation and delivery Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are one indicator of health development in the 2015-2019 RPJMN and SDGs. The maternal mortality rate has increased again to 359 per 100,000 live births. For IMR it can be said that the decline on the track (continues to decline) and in the 2012 IDHS shows 32 / 1,000 KH (2012 IDHS). And in 2015, based on 2015 SUPAS data both AKI and AKB showed a decrease (AKI 305 / 100,000 KH; AKB 22.23 / 1000 KH) From 64 respondents obtained 10.9% experienced mild anxiety, 70.3 % moderate anxiety, and 18.8% severe anxiety. The purpose of this study is to know the effect of giving prenatal yoga to the level of anxiety of pregnant women facing friendship at Balai Krakatau Langkapura Clinic in Bandar Lampung City in 2019.Quantitative research type, research design Quasy Experiment with the posttes only control group approach. The population was 44 respondents and a sample of 32 respondents by division, 16 respondents in the intervention group, and 16 respondents in the control group, a purposive sampling technique alongside data analysis using univariate and bivariate, with a statistical t-test.The average anxiety in the prenatal yoga group with a mean of 26.81 and a standard deviation of 4.833 with the lowest anxiety score 21 and the highest anxiety 38, and in the group not given prenatal yoga with a mean of 42.88 standard deviations of 5.818, with a score of lowest anxiety 30 and the highest anxiety 52. ​​Statistical test t-test results obtained p-value = 0.000 <0.05 which means that there is an influence of giving prenatal yoga with anxiety levels in pregnant women facing relationship. Suggestions for midwives at the Krakatau Clinic to partner with psychology to see the anxious events in TM III pregnant women who will undergo childbirth, to provide counseling or actions that can reduce anxiety in the mother. Keywords: yoga relaxation; anxiety levels; pregnant women; preparation and delivery Angka Kematian Ibu (AKI) dan Angka Kematian Bayi (AKB) merupakan salah satu indikator pembangunan kesehatan dalam RPJMN 2015-2019 dan SDGs. Angka Kematian Ibu meningkat kembali menjadi sebesar 359 per 100.000 kelahiran hidup. Untuk AKB dapat dikatakan penurunan on the track (terus menurun) dan pada SDKI 2012 menunjukan angka 32/1.000 KH Dan pada tahun 2015, berdasarkan data SUPAS 2015 baik AKI maupun AKB menunjukan penurunan (AKI 305/ 100.000 KH; AKB 22,23/ 1000 KH) (Direktorat Kesehatam Keluarga, 2016) Dari 64 responden diperoleh 10.9% mengalami kecemasan ringan, 70,3% kecemasan sedang, dan 18,8% kecemasan berat. Tujuan penelitian diketahui pengaruh pemberian prenatal yoga dengan tingkat cemas ibu hamil menghadapi persalianan di Klinik Balai Krakatau Langkapura Kota Bandar Lampung Tahun 2019.Jenis penelitian kuantitatif, Rancangan penelitian Quasy Eksperiment dengan pendekatan posttes only control grup. Populasi sebanyak 44 responden dan sampel 32 responden dengan pembagian, 16 responden kelompok intervensi, dan 16 responden kelompok kontrol, teknik sampling purposive samping analisa data menggunakan univariat dan bivariate, dengan uji statistik t-tes.Rata-rata kecemasan pada kelompok prenatal yoga dengan mean sebesar 26,81 dan standar deviasi 4,833 dengan skor kecemasan terendah 21 dan kecemasan tertinggi 38, dan pada kelompok yang tidak diberi yoga prenatal dengan mean sebesar 42,88 standar deviasi 5,818, dengan skor kecemasan terendah 30 dan kecemasan tertinggi 52. Uji statistic t-test didapat hasil p-value = 0.000<0.05 yang artinya terdapat pengaruh pemberian prenatal yoga dengan tingkat cemas pada ibu hamil menghadapi persalianan. Saran bagi bidan di Klinik Krakatau untuk bermitra dengan psikologi untuk melihat kejadian cemas pada ibu hamil TM III yang akan menjalani persalinan, untuk memberikan penyuluhan atau tindakan yang dapat mengurangi kecemasan pada ibu.